Effects on learners' performance of using selected and open network resources in a problem-based learning activity - Hsu, Ching-Kun; Hwang, Gwo-Jen; Chuang, Chien-Wen; Chang, Chih-Kai (British journal of educational technology, 2012)
Owing to the popularity of computers and computer networks, fostering the web‐based problem‐solving ability of students has become an important educational objective in recent years. This study attempted to compare the effects of using selected and open network resources on students' intentions with regard to their information system usage by means of technology acceptance model (TAM) questionnaires and learning effectiveness by analysis of covariance of tests in web‐based problem‐solving activities. An experiment was conducted by situating students from a senior high school computer course in web‐based learning environments with open or selected resources to find the answers to several questions about ”structured programming design.” The experimental results showed that in either the open‐resource network or the selected‐resource network, low‐achievement students made remarkable progress. Moreover, the high‐achievement students who learned in the selected‐resource network had significantly better performance than those who learned in the open‐resource network. In addition, the learning task completion ratio and the difficulties the students encountered were recorded and analyzed, and the perceptions of the students regarding their engagement in the learning activity are compared and discussed based on the TAM. Practitioner Notes What is already known about this topic • Problem‐based learning has been recognized as being an important instructional strategy. • The provision of web‐based problem‐solving instructions has the potential to enhance and sustain the problem‐solving skills of the learners. • Searching for information to solve problems has been categorized as involving higher‐order cognitive processes. • Fostering students to develop problem‐solving competences is helpful to them in efficiently learning the subject content. What this paper adds • Investigating whether different information‐searching environments (open and selected network resources) affect the students' web‐based problem‐solving performance. • Investigating whether different information‐searching environments affect the learning achievements of the students after participating in the web‐based problem‐solving activity. • Investigating the students' degrees of acceptance of the information‐searching environments and the correlations between the variables in the environments. Implications for practice and/or policy • Both selected‐ and open‐resource networks are helpful to low and midability students in improving their learning performance. • Investing in the selected resources should improve significantly the high‐achieving students' performance in comparison with using the open resources. • Digital libraries can be put into use in conducting web‐based problem‐solving activities more widely and are worth developing. • Governments or teaching institutes are encouraged to establish digital learning centers and develop digital libraries in which there are many well‐prepared and correct instructional databases for learners to search or consult.